The Dead Sea scrolls at 60 : scholarly contributions of New York University faculty and alumni - Schiffman, Lawrence H.; Tzoref, Shani. (Studies on the Texts of the Desert of Judah, 2010)
This volume constitutes the proceedings of the March 7, 2008 Ranieri Colloquium on Ancient Studies at New York University, dedicated to \'The Dead Sea Scrolls at 60: The Scholarly Contributions of NYU Faculty and Alumni.\' These studies offer a sampling of the extensive research conducted by three generations of NYU faculty, students, and alumni, in a range of domains pertaining to the scrolls and documents discovered in the Judean Desert since 1947, including Hebrew language, religious thought, and law.